Bulgaria Early Childhood Development : SABER Country Report 2013 - World Bank (Washington, DC, 2014)
This report presents an analysis of the early childhood development (ECD) programs and policies that affect young children in Bulgaria and recommendations to move forward. This report is part of a series of reports prepared by the World Bank using the systems approach for better education results (SABER)-ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in Bulgaria, along with regional and international comparisons. The Government of Bulgaria (GoB) recognizes the critical importance of ECD through the range of national laws and regulations in place to promote the provision of adequate early childhood interventions. The present SABER ECD analysis is intended to identify achievements, as well as gaps, in Bulgarian ECD policies and programs in hopes of informing the improvement of the existing ECD system.